The Influence Of K-Pop Artist As Brand Ambassador On Affecting Purchasing Decision and Brand Loyalty (A Study Of Scarlett Whitening’s Consumers in Indonesia) - Bonita Pardede; Atik Aprianingsih (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
One of the current promotional strategies adopted by many brands in Indonesia is leveraging the K-Wave (Hallyu) phenomenon. Scarlett Whitening aims to capitalize on this opportunity by appointing the popular K-Pop girl group, Twice, as their brand ambassador. The significant investment involved in this collaboration raises high expectations for Scarlett Whitening, particularly in terms of the impact that their chosen brand ambassadors have on purchasing decisions and brand loyalty. Hence, the objective of this research is to examine the influence of various dimensions (visibility, credibility, attractiveness, and power) of K-Pop artist Twice on the purchasing decisions and brand loyalty of Scarlett Whitening consumers. Furthermore, the study aims to investigate the mediating role of customer satisfaction in the relationship between purchasing decisions and brand loyalty among Scarlett Whitening consumers. This research employs a non-probability purposive sampling technique, with a sample size of 200 respondents aged between 15 and 34 years, encompassing all genders. The respondents are required to have prior experience using Scarlett Whitening products and possess awareness of Twice as one of Scarlett Whitening's brand ambassadors. The data analysis technique employed is the Structural Equation Modeling (SEM) Partial Least Squares (PLS) method. The findings indicate that the dimensions of